Coenzyme Q 10 (ubiquinone) and brain diseases - connection with the eye and the body - Pavlović, Dragan (Engrami, 2021)
Coenzyme Q10 (CoQ10; ubiquinone) is a vitamin-like substance that is involved in the respiratory chain in the mitrochondria. Ubiquinone is synthesized in all tissues, but with age, the content decreases, as well as in some pathological conditions and with the use of statins. Ubiquinone is necessary for the growth and maintenance of cells in the human body, and with age, food intake is desirable, because endogenous synthesis is no longer sufficient. CoQ10 participates in oxidative phosphorylation and adenosine triphosphate (ATP) production and is a potent antioxidant. Primary CoQ10 deficiencies manifest as multisystem disease, encephalomyopathy, cerebellar ataxia, myopathy, and nephrotic syndrome. In the case of CoQ10 deficiency, reactive oxygen species occur first, and in the case of severe deficiency, the loss of ATP. CoQ10 deficiency also causes apoptosis which is found in the brain and retina of the elderly. CoQ10 deficiency contributes to heart muscle dysfunction in chronic heart failure. The effects of CoQ10 deficiency are inflammation and oxidative stress. An inverse relationship between serum CoQ10 and the risk of developing dementia has been shown. CoQ10 administration resulted in a reduction in depression in patients with metabolic syndrome as well as an improvement in concentration in schizophrenia and schizoaffective disorder. CoQ10 deficiency may be associated with the occurrence of static myopathy. In people with primary CoQ10 deficiencies, there is retinopathy, and in acquired macular degeneration and glaucoma, CoQ10 levels are reduced. High doses of CoQ10 help survive chronic heart failure and coronary heart disease. Beneficial effects of CoQ10 on the treatment of obesity, oxidative stress, metabolic syndrome, type II diabetes mellitus and non-alcoholic fatty liver have been shown. Fatigue applications are controversial. There has been some positive effect of CoQ10 in breast cancer. Studies indicate that the use of CoQ10 has beneficial effects in the early stages of sepsis. For therapeutic purposes, CoQ10 is administered in doses of 30-3000 mg. Doses of 22 mg daily to 400 mg/day are considered safe. Side effects are mostly mild and rare.